2015
DOI: 10.1039/c5cp03097h
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the sterol aliphatic side chain on membrane properties: a molecular dynamics study

Abstract: Following a recent experimental investigation of the effect of the length of the alkyl side chain in a series of cholesterol analogues (Angew. Chem., Int. Ed., 2013, 52, 12848-12851), we report here an atomistic molecular dynamics characterization of the behaviour of methyl-branched side chain sterols (iso series) in POPC bilayers. The studied sterols included androstenol (i-C0-sterol) and cholesterol (i-C8-sterol), as well as four other derivatives (i-C5, i-C10, i-C12 and i-C14-sterol). For each sterol, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 82 publications
2
8
0
Order By: Relevance
“…Consistent with a previous AAMD simulation[45] and experiment [46], our simulations indicated that cholesterol’s aliphatic chain length has little effect on phase separation but significantly alters inter-leaflet coupling and domain registration. A major source of this effect is the impact of the aliphatic chain on interaction of lipids across the bilayer mid-plane.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with a previous AAMD simulation[45] and experiment [46], our simulations indicated that cholesterol’s aliphatic chain length has little effect on phase separation but significantly alters inter-leaflet coupling and domain registration. A major source of this effect is the impact of the aliphatic chain on interaction of lipids across the bilayer mid-plane.…”
Section: Resultssupporting
confidence: 89%
“…In summary, we used coarse-grained MD simulations to quantitatively characterize the effect of cholesterol aliphatic chain length on lipid domain stability and dynamics using a three-component model membrane made up of DPPC, DLiPC, and analogs of cholesterol with various aliphatic chain lengths. Consistent with a previous AAMD simulation [45] and experiment [46], our simulations indicated that cholesterol's aliphatic chain length has little effect on phase separation but significantly alters interleaflet coupling and domain registration. A major source of this effect is the impact of the aliphatic chain on interaction of lipids across the bilayer midplane.…”
Section: Resultssupporting
confidence: 89%
“…For the main set of simulations, the topology of the POPC molecule consisted of an united united-atom description for CH, CH 2 , and CH 3 groups, based on the parameters presented by Berger et al [29] for 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC), adapted to take into account the changed parameters for the double bond in the sn-2 acyl chain, as described elsewhere [30,31]. The unitedatom structure and topology of cholesterol were adapted from those of Höltje et al [32] (available for download at the GROMACS webpage, http://www.gromacs.org/@api/deki/files/29/=cholesterol.tgz) by changing the atom types from CH2/CH3 to LP2/LP3 to avoid overcondensation of the bilayer, as previously suggested [33,34] and validated by ourselves in previous studies [35,36]. The starting structures were POPC (128 molecules) or POPC:20 mol% cholesterol (96 POPC:24 cholesterol) bilayers [37], fully hydrated with N40 water molecules per phospholipid.…”
Section: Methodsmentioning
confidence: 99%
“…15 This result was also confirmed by recent molecular dynamics (MD) simulations. 16 Sterols bearing an unbranched side chain also promote lipid condensation, but to a lesser extent than the native branched iso-alkyl chain of cholesterol. 17 There is relatively little published work on the structural and dynamical aspects of the aliphatic side chain of cholesterol as opposed to the large body of literature on the order and dynamics of phospholipid chains.…”
Section: Introductionmentioning
confidence: 99%